Peningkatan Pemahaman Konsep Matematis Siswa Menggunakan Model Problem Based Learning Kelas XI SMAS Al-Ulum Medan - Ahyar Munawar Khalid (Universitas Islam Sumatera Utara, 2022)
In class XI at SMA Al-Ulum Medan, the goal of this study is to ascertain whether students' understanding of mathematical topics has improved as a result of employing a problem-based learning approach. Students of SMA Al-Ulum Medan's class XI served as the research's subjects, and the problem-based learning paradigm was the study's focus. PTK was the methodology utilized with a sample of 35 class XI students from Al-Ulum Medan Private High School. The Two-Variable Linear Inequality and the Two-Variable Linear Inequality System were examined during the two cycles of this study. Â In the first cycle of learning, there were 15 students who finished with a percentage of 44.12%, and there were 20 students who did not finish with a percentage of 58.82% and an average value of 66.29. (low category). Learning in cycle II saw 14 students drop out with a percentage of 41.18% and an average score of 75.26, while 21 students completed their studies with a percentage of 61.76%. (enough category). As a result, the problem-based learning approach can help pupils better understand mathematical ideas.